2023
DOI: 10.1186/s12871-022-01961-6
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram for predicting the mortality of patients with type 2 diabetes mellitus complicated with acute kidney injury in the intensive care unit

Abstract: Background There is no predictive tool for type 2 diabetes mellitus (T2DM) patients with acute kidney injury (AKI). Our study aimed to establish an effective nomogram model for predicting mortality in T2DM patients with AKI. Method Data on T2DM patients with AKI were obtained from the Medical Information Mart for Intensive Care III. 70% and 30% of the patients were randomly selected as the training and validation cohorts, respectively. Univariate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…ROC curve showed that the AUC of RRI predicting the occurrence of AKI within 72 h was 0.751, which was consistent with Liu’s study [ 21 ]. RrSO2 has a reasonable specificity for the diagnosis of AKI.…”
Section: Discussionsupporting
confidence: 89%
“…ROC curve showed that the AUC of RRI predicting the occurrence of AKI within 72 h was 0.751, which was consistent with Liu’s study [ 21 ]. RrSO2 has a reasonable specificity for the diagnosis of AKI.…”
Section: Discussionsupporting
confidence: 89%
“…Reports suggest that 80% of AKI cases worldwide originate in developing countries, with Southeast Asia exhibiting the highest prevalence at 31%. 1,2 AKI is characterized by a sudden onset of diminished kidney function, typically manifested by a decline in serum creatinine levels or urine output within a span of hours to days. 3 Etiologies of AKI are diverse, including ischemia, infection, exposure to nephrotoxic agents, among others.…”
Section: Introductionmentioning
confidence: 99%